Indebted: How to support countries heavily reliant on oil and gas revenues to secure long-term prosperity - Shandelle Steadman; Ipek Gençsü; Shakira Mustapha; Sarah Colenbrander; Judith Tyson (Overseas Development Institute (ODI), 2023)
This report explores the relationship between oil and gas dependency and a country's debt burden, where repayments are potentially reliant on fossil fuel revenues. In particular, by looking at the interaction between oil and gas prices and public finances over a 11-year period (2010-2020) for a sample of 21 low- and middle-income countries that are highly dependent on oil and gas revenue, it examines how a country's oil and gas dependency interacts with the level, composition and cost of government debt. By better understanding these links, it is possible to identify ways for countries to break the cycle of reliance on oil and gas exports and increasing debt burdens, and to plan for a timely and just energy transition that is aligned with climate goals.
Keywords: 330; Economic growth; Energy; Environment; Public financial management; Climate finance; Climate change; Debt